Penyuluhan Pencegahan Infeksi Saluran Pernafasan Akut Duct Infection Prevention Counseling Acute Breathing - Nurhikmah Nurhikmah; Reskiawati Azis; Nur Aliya Arsyad; Mulyana (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Acute respiratory tract infection) is the most commonly reported disease to the health service. The World Health Organization (WHO) estimates the incidence of Acute Respiratory Infections (ISPA) in developing countries with a mortality rate of toddlers above 40 per 1000 live births is 15%-20% per year in the toddler age group. According to who ± 13 million children under five die each year and most of those deaths are in developing countries ISPA is one of the leading causes of death killing ± 4 million children under five each year. The purpose of The Devotion is to increase public knowledge about ISPA prevention. The method used is socialization by holding counseling. The implementation of this Service at The Makassar City Cotton Health Center with the number of participants as many as 34 mothers. From the results of the extension, there is an increase in public knowledge about the prevention of ISPA so it is expected that this training activity can be carried out throughout the health center work area with government support.